Molecular Mechanisms of Curcumin Renoprotection in Experimental Acute Renal Injury - Fan, Youling; Chen, Hongtao; Peng, Huihua; Huang, Fang; Zhong, Jiying; Zhou, Jun (Frontiers in Pharmacology, 2017)
As a high perfused organ, kidney is especially sensitive for ischemia and reperfusion. Ischemia-reperfusion (IR)-induced acute kidney injury (AKI) has been a high incidence of perioperative period in the clinic, which is the important link of ischemic acute renal failure (ischemic acute takes its failure, IARF). Therefore, it has important clinical significance to explore the mechanism of IR-induced AKI and administrate drugs to prevent and alleviate damage. Curcumin [diferuloylmethane, 1,7-bis(4-hydroxy-3-methoxiphenyl)-1,6-heptadiene-3,5-dione)] is a polyphenol compound derived from curcuma longa (turmeric). It had been reported that curcumin plays a renoprotective effect on ischemia-reperfusion injury in previous study. However, the specific mechanisms of protective role with curcumin underlying IR-induced AKI are not completely revealed. APPL1 is a protein coding gene which has been shown to be involved in crosstalk between the adiponectin-signaling and insulin-signaling pathways. In this study, we determined that the renoprotective of curcumin in the experimental models of IR-induced AKI via reducing apoptosis and found that APPL1 and phosphorylated Akt were significantly upregulated in the kidney. Our results of in vitro experiments exhibited that apoptosis of renal tubular epithelial cells were exacerbated with hypoxia-reoxygenation (HR) treatment compared with sham control cells. Curcumin significantly decreased apoptosis rate of renal tubular epithelial cells with HR treatment. Moreover, knockdown of APPL1 activated Akt and then aggravated apoptosis in HR treated renal tubular epithelial cells, while inhibition of Akt could directly reverse the effects of APPL1 knockdown. In summary, our study demonstrated that curcumin mediating upregulation of APPL1 protects against ischemia reperfusion induced acute kidney injury through inhibiting phosphorylation of Akt.